Searching for hidden bridges in co-occurrence networks from Javanese wayang kulit - Schauf, Andrew Johnathan (Journal of historical network research, 2018)
We propose that questions of long-standing interest in the study of wayang kulit, Indonesia's centuries-old shadow puppet theater tradition, can potentially be posed in structural terms and investigated using the tools of network science. Here, we construct weighted character co-occurrence networks based on the Javanese wayang kulit incarnation of the Mahabharata epic, supplementing nodes with metadata specifying characters' tribal affiliations and historical origins in either Indian or Javanese traditions. In order to identify characters who play unique structural roles which other approaches may overlook, we generate null model ensembles of artificial networks that share the empirical networks' degree sequences, underlying episodic structures, and node metadata. By ranking nodes by the extent to which their betweenness centrality exceeds a null model's expectations, we reveal characters whose appearances in a story, while not necessarily large in number, tend to serve the specific topological function of bridging groups of other characters. Decomposing betweenness centrality values into their inter-faction components then clarifies how these bridge-like characters are situated among the epic's various social factions. We observe that female characters, despite being few in number and appearing relatively infrequently, appear to dominate these rankings disproportionately. Analyses involving closeness centrality reveal low-closeness outliers whose appearances, although relatively frequent, keep them structurally isolated and distant from the rest of the Mahabharata universe; these include the epic's antagonists, the Korawa. Characters with historical origins in the Javanese tradition are found to be embedded just as closely within the network as are characters from the Indian canon when their degrees are taken into account using null models.